Religious and educational services of Said Nursi: Research Review: سعید نورسی کی دینی و تعلیمی خدمات:تحقیقی جائزہ - Parveen, Dr. Zakra (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Said Nursi was the prominent scholar of the 20th century. He worked for betterment of Islam. He was in favor of modern education in Turkey that was why he gave his own education system which was the blend of traditional and modern concepts of education. In spite of the resistance of traditional religious scholar, he did not leave his struggle for harmonize the Islam to modern trends. In this article, humble effort is made to highlight his religious and educational services.